Mass mortality events associated with cyprinid herpesvirus 2 ( CyHV ‐2) infection in wild Prussian carp Carassius gibelio in the Netherlands, and molecular biology of virus strains - Tomofumi Kurobe; Jun Kurita; Olga Haenen; Michal Voorbergen‐Laarman; Takafumi Ito (Journal of Fish Diseases, 2024)
In 2011 and 2015, four mass mortalities of Prussian carp ( Carassius gibelio ) were observed in a recreational freshwater lake and open freshwater in the western part of the Netherlands. Cyprinid herpesvirus 2 (CyHV‐2) infection was suspected in these cases, based on presumptive gross diagnosis. To elucidate the cause of the mass mortalities diagnostic PCR assays were performed for CyHV‐2, based on the helicase gene. Furthermore, the viral isolates were genotyped by sequencing the enlarged marker A and marker B sequences. Diagnostic PCR revealed that three of four samples were positive for CyHV‐2, indicating these three mass mortalities were associated with CyHV‐2 infection. The marker A sequence from one of the isolates found in this study was identical to those from different locations such as Asia and Middle East, suggesting a link among the isolates. This is the first detailed report on mass mortalities of Prussian carp associated with CyHV‐2 infection in natural aquatic environments in the Netherlands. Since 2015, additionally, in total three CyHV‐2 associated outbreaks of Dutch Prussian carp were seen in 2016 and 2020. These outbreaks in Prussian carp from lakes and open water suggest that the virus has been spreading in natural freshwaters in the Netherlands.